Sosialisasi Produk Halal Dan Proses Sertifikasi Produk Halal : Desa Ngujang, kecamatan Kedungwaru, Kabupaten Tulungagung, Jawa Timur - Yulian Adi Wijaya; Chavid Moyo Jaladri (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2021)
Kedungwaru District is home to a plethora of food booths and other culinary businesses. The Muslim population in Kedungwaru sub-district is still underserved. The Regional Culinary Entrepreneurs Network (JPKD) and the Archipelago Culinary Business are two SME partners in the project. Both are associations of food and beverage enterprises, such as restaurants, restaurants, and SMEs that provide and produce ready-to-eat food. JPKD is from Ngujang Village in Kec. Kedungwaru is from Tulungagung district. Milk pie bread is one of the food products that must be halal before being given to the general public. Mrs. ela distanika, whose address is at Street Keras, Kediri Regency, owns one of the tiny enterprises that creates milk pie. This activity’s goal is to help SMEs acquire halal certification. Internal audit training is followed by the preparation of supporting documents for halal certification, the implementation of a halal assurance system, the registration of CEROL (Certificate On Line) at LPPOM MUI district, which is then extended to East Java province, and the auditing process by halal auditors. This activity was successful in assisting with registration and the auditing process. What must be examined is business actors’ commitment to applying the Halal Assurance System. The production unit is improved so that it may be separated from the home.